General conception of the studies of mathematics and their successful realization at Vilnius Pedagogical University - Banys, Jonas; Griniuvienė, Liucija; Naudžiūnienė, Vanda (Lietuvos matematikos rinkinys, 2023)
In this paper enrolment and study problems in the faculty of Mathematics and informatics of Vilnius Pedagogical university are discussed.
Keywords: student; studies; questioning; standpoint